Genetic differentiation of European anchovy (Engraulis encrasicolus) along the Moroccan coast reveals a phylogeographic break around the 25th parallel North. Issue 3 (16th March 2017) - Chahdi Ouazzani, Khalil; Benazzou, Touria; Charouki, Najib; Bonhomme, François; Chlaida, Malika
ABSTRACT: Seven microsatellite markers were used to investigate the population structure of the offshore ecotype of the European anchovy ( Engraulis encrasicolus ) by comparing 12 marine samples collected off the Moroccan coast with an inshore sample taken as a reference for the lagoonal ecotype. F -statistics, correspondence analysis and Bayesian assignment all concurred to cluster the European anchovy in this region into three groups: (i) one reference lagoonal sample, (ii) samples north of the 25°N latitude and (iii) samples south of it. Moreover, the Bayesian cluster analysis pointed toward the existence of an admixture between the group north of 25°N and the lagoonal ecotype, while this was not detectable with the group south of 25°N. Differential introgression between the two ecotypes could be one of the plausible explanations for the observed genetic structure and reveals the possible existence of a phylogeographic break around the 25th parallel North. Our study illustrates the fact that, for those species that encompass several incompletely isolated ecotypes, the level of gene flow among them may vary in space and serve as a tool for stock identification. This information may be useful to improve fishery management of this important harvested species along the Moroccan coast.